Landslide Potential Zone Identification Using Electrical Resistivity Tomography Modeling - Alghifarry, Muhammad Budzar; Dewanto, Ordas; Wibowo, Rahmat Catur (Journal of Engineering and Scientific Research, 2023)
The Pidada area, Panjang sub-district, Bandar Lampung City, is located on the physiography of Bukit Barisan and is also influenced by the movement of the Sumatran fault and the Lampung-Panjang fault, so the morphological condition is hilly with steep slopes which cause natural disasters such as landslides. In this study, the knowledge of subsurface rock lithology and slip-slide-prone zones was carried out using the Wenner-Schlumberger geoelectric method. Based on the Wenner-Schlumberger configuration, the top layer consists of weathered rock associated with clay tuff and sandy tuff with a resistivity of 7.2 ?m - 135 ?m. Coarse-grained tuff and fine-grained tuff with resistivity values ??of 135 ?m - 437 ?m, and the third layer combines breccia and igneous rock from the Tarahan Formation with resistivity values ??of more than 437 ?m. The clay sand layer acts as a slip plane. The type of landslide developed in the research area is a crawling soil landslide.